2013
DOI: 10.4236/ojog.2013.37105
|View full text |Cite
|
Sign up to set email alerts
|

The effect of administrating hyoscine bromide on pregnancy rate before embryo transfer in ART cycles

Abstract: Assisted reproductive technology methods i.e., IVF and ICSI were extensively used for treatment of infertility. Although, these methods have many advantages but ART pregnancy rate remains low (30%-35%). It seems that uterine peristalsis occurred after rhCG administration in turn resulting to impair implantation of the transferred embryos. Therefore this study was conducted to possess of whether hyoscine bromide can effectively alleviate uterine contraction and then have any effect on the reproductive outcome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…A meta-analysis of two small placebo-controlled RCT (Sohrabvand et al, 2009;Zargar et al, 2013) also showed this positive effect on pregnancy rates: RR 1.82 (1.10-3.03), I 2 : 35% (Figure 7; low quality of evidence: Table 4). Beta-adrenergic receptor antagonists such as ritodrine and terbutaline are well known for reducing UC in the pregnant uterus (de Heus et al, 2008).…”
Section: Treatment Optionsmentioning
confidence: 90%
“…A meta-analysis of two small placebo-controlled RCT (Sohrabvand et al, 2009;Zargar et al, 2013) also showed this positive effect on pregnancy rates: RR 1.82 (1.10-3.03), I 2 : 35% (Figure 7; low quality of evidence: Table 4). Beta-adrenergic receptor antagonists such as ritodrine and terbutaline are well known for reducing UC in the pregnant uterus (de Heus et al, 2008).…”
Section: Treatment Optionsmentioning
confidence: 90%
“…However, despite the fact that assisted reproductive technology (ART) has experienced rapid developments over the past several years, pregnancy rates using these techniques remain relatively low. 1,2 Recurrent implantation failure (RIF) is one of the most common causes of pregnancy failure after receiving ART. 3 The RIF is diagnosed when clinical pregnancy failure occurs after 2 consecutive IVF-ETs to the endometrium using at least 4 high-quality embryos.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the fact that assisted reproductive technology (ART) has experienced rapid developments over the past several years, pregnancy rates using these techniques remain relatively low. 1,2…”
Section: Introductionmentioning
confidence: 99%
“…Three studies reported the findings of trials investigating the use of the nitric oxide donor in the form of nitroglycerin patch (Farzi et al, 2005;Ohl et al, 2002;Shaker et al, 1993) and two studies investigated the use of the antimuscarinic agent Hyoscine (Sohrabvand et al, 2009;Zargar et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Many randomized controlled trials (RCTs) have been conducted to evaluate the efficacy of these drugs when administered in the peri-implantation period of assisted reproduction technique cycles (Bernabeu et al, 2006;Dal Prato and Borini, 2009;Farzi et al, 2005;Firouzabadi et al, 2007;Hanevik et al, 2012;Moraloglu et al, 2010;Ng et al, 2014;Ohl et al, 2002;Pinheiro et al, 2003;Shaker et al, 1993;Tsirigotis et al, 2000;Zargar et al, 2013). The results of these trials, however, have been conflicting.…”
Section: Introductionmentioning
confidence: 99%